Analisis intertekstual Roma 9:33 Suatu Pendekatan Memori Semantik Pada Teologi Paulus - Asnita Basir Leman (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2023)
Romans 9:33 is known as a very complicated verse with Old Testament intertextual quotations from Isaiah 8:14 and 28:16 in splits and crosses. The use of allusions as key words such as